Oropharyngeal CSF Leak Secondary to Anterior Cervical Discectomy and Fusion - Wyatt J. Weinheimer; Justin G. Rowley; Randal Otto; John Floyd; Philip G. Chen (Case Reports in Otolaryngology)
We present a case of an oropharyngeal cerebrospinal fluid (CSF) fistula in a patient that presented with headache, rhinorrhea, and pneumocephalus years after an anterior cervical discectomy and fusion. Imaging suggested a defect in the fovea ethmoidalis, but endoscopic surgery revealed the defect in the oropharynx. A second procedure was performed to remove the spinal hardware and repair the leak. This case is not only unique in the literature but also highlights the importance of maintaining a broad differential diagnosis to include rare complications and shows that despite dramatic improvements in imaging, locating CSF leaks still presents a challenge.